CAN ACCOUNTING INFORMATION ACT AS A PROXY FOR EX ANTE UNCERTAINTY IN INITIAL PUBLIC OFFERINGS? - Gumanti, Tatang Ary (Master of Management, Faculty of Economics and Business, Universitas Gadjah Mada, 2003)
This paper reviews and summarizes previous works and the rationale for the proposition that accounting information is in fact value relevant in the determination of an initial public offering IPO).Theoretical and empirical evidence has indicated that certain accounting measures can he used as proxies for total firm risk, that is, they could determine the riskiness of a corporation. The literature also advocates that accounting information is relevant in determining the value and thus the riskiness of a corporation through the use of accounting analysis. Since most of the information available in the prospectus is accounting information, it is arguable that this information represents a potential source for assessing the issuing firm. Some scholars have also advocated the possibility of using accounting information in assessing the value of firm making an IPO. Numerous papers have provided analytical and empirical evidence of the association between accounting numbers and the value of IPOs. The conclusion generally comes to show that information in the prospectus is value relevant concerning the IPO. The paper shows that it is indeed an arguable to use accounting information in the valuation of an IPO. Accordingly, it is an empirical issue whether accounting information has the property in explaining the ex-ante uncertainty of an IPO.